Sweden and the Baltic Sea Region Co-operation. Contribution to Territorial Cohesion and Sustainable Development together with the new Member States and Russia. Schweden und die Kooperation im Ostseeraum. Gemeinsam mit den neuen EU-Staaten und Russland zur territorialen Zusammenarbeit und nachhaltigen Entwicklung beitragen. - Löwendahl, Bo; Persson, Per-Olof; Karlson, Rolf A.; Engström, Carl-Johan (Bundesamt für Bauwesen und Raumordnung, 2005)
Der Beitrag betont die Notwendigkeit einer dauerhaften transnationalen Zusammenarbeit in sog. Makroregionen (großen Entwicklungszonen), die die benachbarten Subregionen entlang der Ostsee in ihren Bemühungen um eine sozioökonomische und räumliche Entwicklung miteinander verbindet. Die Ausführungen beruhen auf Ergebnissen von drei Projekten in Makroregionen: Baltic+, Baltic Palette, Seagull. Gemeinsame Merkmale der Projekte, vor allem von Baltic+ und Seagull, sind ihre Orientierung an bestehenden Euroregionen und die Einbindung alter wie neuer Mitgliedstaaten im südlichen Ostseeraum. Im dritten Projekt (Baltic Palette) wurde die Gelegenheit genutzt, eine neue politische Netzwerkregion zu bilden, um aus den Gateway-Funktionen im Kern der Ostseeregion Kapital zu schlagen. Alle drei Projekte zeitigen wertvolle Ergebnisse. Die politischen und professionellen Netzwerke wurden gefestigt, und geplant ist, noch konkretere Themen aufzugreifen und die Grundlage für eine nächste Phase mit strategischen Investitionen zubereiten. Eine Reihe von wichtigen Fragen richten sich an die nachfolgenden transnationalen EU-Programme zur räumlichen Zusammenarbeit (2007-2013): Wird das kommende Programm diese Art Projekten zu Makroregionen/großen Entwicklungsachsen unterstützen? Wie könnte eine Zusammenarbeit der EU-Mitgliedstaaten mit benachbarten Nichtmitgliedsländern wie Russland und Weißrussland die Kooperation in Zukunft stärken? difu

The article stresses the need of continuing trans-national co-operation in macro-regions (large development zones), linking neighbouring sub-regions across the Baltic Sea within the long-term engagement in socioeconomic and spatial development. The reflections are focused on the results from three macro-region projects that are still ongoing or about to be finalized: Baltic+. Baltic Palette, Seagull. The common characteristics of these projects are their connection to existing political Euroregions and their comprising of old and new member states in the southern part of the Baltic Sea (Baltic+ and Seagull). The third case (Baltic Palette) has grasped the opportunity to create a new political networking region in order to capitalize on the gateway functions in the core of the BSR. The three macro-region projects have achieved valuable results. Their political and professional networks were consolidated and there are ambitions to develop more concrete topics and to prepare the ground for strategic investments in the next phase. The projects will strengthen the capacity building of local and regional institutions in order to ensure the implementation of the results. Such institutions will also be able to improve joint management of new themes of cross-frontier nature, e.g. water management, risk management, maritime safety, urban networks and innovative thematic clusters of various types. A number of important issues for the succeeding trans-national programmes on territorial co-operation (2007-2013) are raised. Will the following programme support this kind of macro-regional/large development zone projects? How could co-operation between EU Member states and the external neighbouring countries such as Russia/Belarus be able to strengthen co-operation in the future? Regarding EuroRegion Baltic (ERB) it is fundamental to get Kaliningrad oblast fully participating in all ERN activities. difu
Keywords: Raumordnung; Raumentwicklung; Kooperation; Investition; Großraum; Netzwerk; Internationale Zusammenarbeit; Mitgliedstaat; EU-Erweiterung; Projekt; Makroregion; Programm; Makroregion